2018
DOI: 10.31674/mjn.2018.v10i01.014
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Compliance With Infection Control Measures and Barriers to Precautions in the Delivery Room

Abstract: Background: Nurses play crucial role in avoiding hospital procured infections, by guaranteeing that all viewpoints of their nursing practice is prove based, and also through nursing inquire research and understanding instruction. Aim: The study aimed to evaluate the nurse's compliance with infection control measures and-barrier precautions in delivery room. Methods: Research design: An exploratory design had been chosen for carrying out our paper. Setting: The study was carried out in four hospitals in Damiett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, nearly two fifth of the studied nurses had nursing diploma, and less than one half was over 40 and had at least 20 years of experience. These results are partially supported by Abdelati, Ali, Yousif, and El-berdan (2018) [28] who revealed that the majority of the nurses in their study were over 30 years old and slightly more than two fifth of them were 40 years or more and they had a diploma in nursing.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, nearly two fifth of the studied nurses had nursing diploma, and less than one half was over 40 and had at least 20 years of experience. These results are partially supported by Abdelati, Ali, Yousif, and El-berdan (2018) [28] who revealed that the majority of the nurses in their study were over 30 years old and slightly more than two fifth of them were 40 years or more and they had a diploma in nursing.…”
Section: Discussionmentioning
confidence: 51%